Powder material and powder material slurry

By using a specific composition of ZnO-B2O3-SiO2-V2O5 glass powder material, the problem of metal formation analysis during firing in an inert atmosphere is solved, and the effect of low-temperature firing and excellent acid resistance is achieved.

CN119461832APending Publication Date: 2025-02-18NIPPON ELECTRIC GLASS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411084543.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art When the glass powder material is fired in an inert atmosphere, metal lead or bismuth may easily precipitate, which will damage the insulating properties.

Method used

The ZnO-B2O3-SiO2-V2O5-type glass powder with a specific composition contains components such as ZnO 20% to 60%, B2O3 10% to 40%, SiO2 5% to 30%, V2O5 0.1% to 13%, and essentially does not contain The softening point of PbO is preferably 640°C or less.

Benefits of technology

It is realized that the powder material is fired at low temperature and is difficult to precipitate metal components in an inert atmosphere, and has excellent acid resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004984787700000081
    Figure BDA0004984787700000081
  • Figure BDA0004984787700000091
    Figure BDA0004984787700000091
Patent Text Reader

Abstract

Provided are a powder material and a powder material slurry which have excellent acid resistance, can be fired at low temperatures, and are unlikely to precipitate a metal component even when fired in an inert atmosphere. The powder material is characterized by containing, as a glass composition, 20%-60% by mole of ZnO, 10%-40% by mole of B2O3, 5%-30% by mole of SiO2, 0.1%-13% by mole of V2O5, 0-4% by mole of Al2O3, 0-5% by mole of Li2O + Na2O + K2O, 0-5% by mole of MgO, 0-13% by mole of CaO, 0-4% by mole of Bi2O3, and 0-1% by mole of Fe2O3, and by containing substantially no PbO.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder material and a powder material slurry, for example, to a powder material and a powder material slurry for forming an outer coating on an electronic circuit or the like. Background Art

[0002] The outer coating is formed to protect and insulate the resistor formed on a substrate such as a soda-lime glass substrate or an alumina substrate. In the past, a powder material slurry was used to form the outer coating. The powder material slurry is usually a mixture of glass powder and a carrier, and ceramic powder is sometimes added as needed.

[0003] The outer coating is formed by firing a powder material slurry applied to a substrate on which a resistor or the like is formed. Here, in order to prevent the characteristics of the resistor or the like from being deteriorated due to the reaction between the resistor or the like and the powder material, the firing temperature is limited to below 650°C. Therefore, it is required that the powder material (powder material slurry) can be fired at a temperature below 650°C. In addition, it is also required that the powder material does not cause the substrate to warp after firing and is not easily peeled off from the substrate.

[0004] In order to give the electronic circuit formed with the outer coating properties such as corrosion resistance, optical properties, mechanical properties, electrical properties, etc., a plating process is sometimes performed. In this plating process, the outer coating is immersed in a plating solution. The plating solution is usually an acidic solution. Therefore, when a plating process is performed, the outer coating is required to be acid-resistant. In other words, the powder material is required to be acid-resistant. It should be noted that in order to adjust the resistance value of the resistor within a certain range, it is necessary to irradiate Nd:YAG, Nd:YVO from the upper part of the outer coating. 4 Near-infrared laser (wavelength: 1064nm) is used to trim the outer coating and part of the resistor.

[0005] As a powder material that meets the above required properties, PbO-B has been used. 2 O 3 -SiO 2 It is glass (see Patent Document 1).

[0006] In recent years, from the perspective of environmental protection, the reduction of environmental load substances, such as PbO, has been promoted, and various lead-free glasses have been proposed to replace PbO-B. 2 O 3 -SiO 2 For example, Patent Documents 2 to 4 describe Bi 2 O 3 -B 2 O 3 -ZnO based glass.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 58-64245

[0010] Patent Document 2: Japanese Patent Application Publication No. 2009-221027

[0011] Patent Document 3: Japanese Patent Application Publication No. 2007-63105

[0012] Patent Document 4: Japanese Patent No. 4598008 Summary of the invention

[0013] Technical problem that the invention aims to solve

[0014] However, when a material that is easily oxidized, such as Cu, is used as a part of the resistor, the powder material slurry is fired in an inert atmosphere such as nitrogen, argon, or helium.

[0015] However, when the glasses described in Patent Documents 1 to 4 are fired in an inert atmosphere, metal lead or metal bismuth is precipitated, which causes a problem that it is difficult to maintain properties such as insulation.

[0016] An object of the present invention is to provide a powder material which has excellent acid resistance, can be fired at a low temperature, and is unlikely to precipitate a metal component even when fired in an inert atmosphere.

[0017] Technical solutions to the problem

[0018] The inventors conducted various experiments and found that: 2 O 3 -SiO 2 -V 2 O 5 The glass powder of the present invention can solve the above technical problems. That is, the glass powder of the present invention is characterized in that, as a glass composition, it contains, in mol%, 20% to 60% of ZnO, 2 O 3 10%~40%, SiO 2 5%~30%,V 2 O 5 0.1%~13%,Al 2 O 3 0~4%、Li 2 O+Na 2 O+K 2 O 0~5%, MgO 0~5%, CaO0~13%, Bi 2 O 3 0~4%、Fe2 O 3 0~1%, and contains substantially no PbO. 2 O+Na 2 O+K 2 O” is Li 2 O、Na 2 O and K 2 The term "substantially free of" means that the component is not intentionally added as a glass component, and does not mean that impurities inevitably mixed in are completely excluded. Specifically, it means that the content of the component including impurities is less than 0.1 mass %.

[0019] The powder material of the present invention preferably has a softening point of 640° C. or less. Here, the “softening point” refers to the value of the fourth inflection point measured by a macro differential thermal analyzer (DTA).

[0020] The powder material of the present invention preferably has a linear thermal expansion coefficient of 50×10 -7 / ℃~80×10 -7 Here, the "linear thermal expansion coefficient" is a value measured in a temperature range of 30 to 300°C by a thermomechanical analyzer (TMA).

[0021] The powder material of the present invention is preferably used to form an outer coating.

[0022] The powder material slurry of the present invention is characterized by containing the above-mentioned powder material and a carrier.

[0023] Effects of the Invention

[0024] According to the present invention, it is possible to provide a powder material which has excellent acid resistance, can be fired at a low temperature, and is unlikely to precipitate a metal component even when fired in an inert atmosphere. DETAILED DESCRIPTION

[0025] The powder material of the present invention is characterized in that, as a glass composition, it contains, in mol%, 20% to 60% of ZnO, B 2 O 3 10%~40%, SiO 2 5%~30%,V 2 O 5 0.1%~13%,Al 2 O 3 0~4%、Li 2 O+Na 2 O+K 2 O 0~5%, MgO 0~5%, CaO 0~13%, Bi 2 O 3 0~4%、Fe 2 O3 0~1%, and substantially no PbO is contained. The following is an explanation of the reasons for limiting the content range of each component as described above. In addition, in the description of the content range of each component, % refers to mole %. In this specification, the numerical range represented by "~" refers to a range that includes the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively.

[0026] ZnO is a component that reduces the softening point and linear thermal expansion coefficient. The ZnO content is 20% to 60%, preferably 35% to 55%, and more preferably 45% to 52%. If the ZnO content decreases, the softening point increases, and it is difficult to sinter at a temperature below 650°C. In addition, the linear thermal expansion coefficient increases, and the stress caused by the difference in linear thermal expansion coefficients between the outer coating and the resistor increases, and the outer coating is prone to cracking. On the other hand, if the ZnO content increases, the acid resistance is easily reduced.

[0027] B 2 O 3 It is a component that forms the glass skeleton and further expands the vitrification range. 2 O 3 The content of B is 10% to 40%, preferably 15% to 35%, and more preferably 18% to 30%. 2 O 3 If the content of B decreases, the thermal stability will be reduced. 2 O 3 As the content of increases, the acid resistance tends to decrease.

[0028] SiO 2 It is a component that forms the glass skeleton and improves acid resistance. SiO 2 The content of SiO is 5% to 30%, preferably 7% to 25%, and more preferably 10% to 22%. 2 On the other hand, if the content of SiO 2 When the content of increases, the softening point increases, and it becomes difficult to perform firing at a temperature of 650°C or lower.

[0029] V 2 O 5 It is a component that improves acid resistance. 2 O 5 The content of V is 0.1% to 13%, preferably 2% to 11%, and more preferably 3% to 9%. 2 O 5 If the content of V 2 O 5 As the content of increases, the thermal stability tends to decrease.

[0030] Al2 O 3 It is a component that improves acid resistance and significantly increases the softening point. 2 O 3 The content of Al is 0-4%, preferably 0.1%-3%, more preferably 0.5%-2%. 2 O 3 If the content of Al decreases, the acid resistance tends to decrease. 2 O 3 When the content of increases, the softening point increases, and it becomes difficult to perform firing at a temperature of 650°C or lower.

[0031] Li 2 O、Na 2 O and K 2 O is a component that lowers the softening point and is a component that lowers acid resistance and thermal stability. 2 O、Na 2 O and K 2 The total amount and individual content of O are 0-5%, preferably 0-2%, and more preferably 0-1%. 2 O、Na 2 O and K 2 When the total amount and individual contents of O increase, the acid resistance and thermal stability tend to decrease.

[0032] MgO is a component that lowers the softening point and is a component that lowers the acid resistance. The content of MgO is 0 to 5%, preferably 0.1% to 4.5%, and more preferably 0.5% to 4%. If the content of MgO decreases, the softening point increases, and it is difficult to sinter at a temperature below 650°C. On the other hand, if the content of MgO increases, the acid resistance tends to decrease.

[0033] CaO is a component that lowers the softening point, stabilizes the glass, and reduces acid resistance. The content of CaO is 0 to 13%, preferably 1% to 12%, and more preferably 3% to 10%. If the content of CaO decreases, the softening point increases, making it difficult to sinter at a temperature below 650°C. On the other hand, if the content of CaO increases, acid resistance tends to decrease.

[0034] Bi 2 O 3 Bi is a component that lowers the softening point without significantly reducing the acid resistance, but is a component that is reduced during firing in an inert atmosphere and is easily precipitated as a metal component. 2 O 3 The content of Bi is 0-4%, preferably 0-3%, and more preferably 0.1%-1%. 2 O 3If the content of Bi decreases, the softening point increases, making it difficult to sinter at a temperature below 650°C. 2 O 3 When the content of increases, metal components are easily precipitated during firing in an inert atmosphere.

[0035] Fe 2 O 3 It is a component that has the effect of improving the thermal stability of glass when used in an appropriate amount, but conversely reduces the thermal stability when used in an excessive amount. 2 O 3 The content of Fe is 0 to 1%, preferably 0 to 0.8%, and more preferably 0.1% to 0.6%. 2 O 3 The content is small and the thermal stability is easily reduced.

[0036] From the viewpoint of environment, it is preferred that PbO is not substantially contained, and F and Cl are not substantially contained.

[0037] In the powder material of the present invention, the softening point is preferably 640°C or less, particularly preferably 635°C or less. If the softening point is too high, the firing temperature must be increased in order to obtain a dense outer coating. In this case, the resistor and the powder material react, and the characteristics of the resistor and the like are easily deteriorated. The lower limit of the softening point is not particularly limited, but is actually 500°C or more.

[0038] In the powder material of the present invention, the linear thermal expansion coefficient is preferably 50×10 -7 / ℃~80×10 -7 / ℃, particularly preferably 53×10 -7 / ℃~70×10 -7 / ℃. In this way, the stress caused by the difference in linear thermal expansion coefficient between the outer coating and the resistor body is reduced, and cracks are less likely to occur in the outer coating.

[0039] In the powder material of the present invention, the average particle size D 50 Preferably less than 3 μm, the maximum particle size D max It is preferably 20 μm or less. 50 , maximum particle size D max If the average particle size D is too large, the smoothness of the outer coating will be easily deteriorated. 50 " refers to the value measured by a laser diffraction device, which indicates the particle size when the cumulative amount reaches 50% from the smallest particle in the volume-based cumulative particle size distribution curve measured by the laser diffraction method. In addition, "maximum particle size D max” refers to a value measured by a laser diffraction device, and indicates the particle size at which the cumulative amount reaches 99% from the smallest particle in a volume-based cumulative particle size distribution curve measured by the laser diffraction method.

[0040] In order to adjust the trimming properties, the powder material of the present invention can also be added with powders such as cordierite, willemite, β-eucryptite, alumina, mullite, zircon, etc. as filler powders. The amount of filler powder added is preferably 0 to 10 parts by mass, 0.1 to 9 parts by mass, and particularly preferably 1 to 8 parts by mass relative to 100 parts by mass of the powder material. If the amount of filler powder added is too much, the proportion of the powder material is relatively small, and it is difficult to form a dense outer coating. It should be noted that from the viewpoint of the smoothness of the outer coating, the average particle size D of the filler powder is preferably 0 to 10 parts by mass, 0.1 to 9 parts by mass, and particularly preferably 1 to 8 parts by mass. 50 It is preferably 0.2 to 10 μm.

[0041] The powder material slurry of the present invention is characterized in that the powder material is the above-mentioned powder material in the powder material slurry containing the powder material and the carrier. Here, the carrier is a material for dispersing the powder material into slurry, and is usually composed of a resin, a plasticizer, a solvent, etc.

[0042] Next, the method for producing the powder material and powder material slurry of the present invention will be described.

[0043] First, molten glass is formed into a film shape, and the obtained glass film is pulverized and classified to prepare a powder material composed of glass (hereinafter referred to as a glass powder material).

[0044] Then, the glass powder material and the vehicle are mixed and kneaded at a predetermined ratio to prepare a powder material slurry. The vehicle may contain, for example, a plasticizer, a dispersant, and the like in addition to an organic solvent and a resin.

[0045] The organic solvent is a material for slurrying the glass powder material, and for example, terpineol (Ter), diethylene glycol monobutyl ether (BC), diethylene glycol monobutyl ether acetate (BCA), 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, dihydroterpineol, etc. can be used alone or in combination. The content of the organic solvent in the carrier is preferably 10% to 40% by mass.

[0046] The resin is a component that increases the strength of the film after drying and imparts flexibility, and its content in the carrier is usually about 0.1% to 20% by mass. The resin can be a thermoplastic resin, specifically, polybutyl methacrylate, polyvinyl butyral, polymethyl methacrylate, polyethyl methacrylate, ethyl cellulose, etc., which can be used alone or in combination.

[0047] The plasticizer is a component that controls the drying speed and imparts flexibility to the dried film, and its content in the carrier is usually about 0 to 10% by mass. As the plasticizer, butyl benzyl phthalate, dioctyl phthalate, diisooctyl phthalate, dioctyl phthalate, dibutyl phthalate, etc. can be used, and they can be used alone or in combination.

[0048] As the dispersant, an ionic dispersant or a nonionic dispersant can be used. As the ionic dispersant, a polycarboxylic acid system such as a carboxylic acid system, a dicarboxylic acid system, an amine system, etc. can be used. As the nonionic dispersant, a polyester condensation type or a polyol ether type dispersant can be used. The amount of the dispersant used in the carrier is usually 0 to 5% by mass.

[0049] When using powder material slurry to form an outer coating, first, the powder material slurry is applied to a substrate on which a resistor or the like is formed by screen printing, batch coating, etc., to form a coating layer of a specified film thickness, and then dried to obtain a dry film. Next, the dry film is fired at a temperature of 550°C to 650°C for 5 to 20 minutes, thereby forming a specified outer coating. It should be noted that if the firing temperature is too low or the firing time (holding time) is too short, the dry film is not fully sintered, and it is difficult to form a dense fired film. On the other hand, if the firing temperature is too high or the holding time is too long, the resistor or the like reacts with the powder material, and the characteristics of the resistor or the like are easily deteriorated.

[0050] As a method for forming the overcoat layer, a method using a powder material slurry has been described as an example, but other methods may be selected, for example, a green sheet method, a photosensitive slurry method, a photosensitive green sheet method, or the like.

[0051] The glass powder material and powder material slurry of the present invention are preferably used to form an outer coating layer of a chip resistor.

[0052] Example

[0053] Hereinafter, the present invention will be described in detail based on the examples. In addition, the present invention is not limited by the following examples. The following examples are only examples.

[0054] Table 1 shows Examples (Samples No. 1 to No. 4) of the present invention and Comparative Examples (Samples No. 5 and No. 6).

[0055] [Table 1]

[0056]

[0057]

[0058] First, the raw materials were prepared in such a way as to obtain the glass composition shown in Table 1 and mixed uniformly. Then, they were placed in a platinum crucible and melted at 1200°C for 2 hours. Then, a portion of the molten glass was poured into a stainless steel mold as a sample for measuring the linear thermal expansion coefficient, and the remaining molten glass was formed into a film using a water-cooled roller. The obtained glass film was crushed with a ball mill and subjected to air flow classification to obtain an average particle size D 50 The maximum particle size is less than 3 μm. max The obtained glass powder material was used to evaluate the softening point.

[0059] The softening point was set to the value of the fourth inflection point measured by a macro differential thermal analyzer (DTA).

[0060] The linear thermal expansion coefficient is obtained by measuring a measurement sample of the linear thermal expansion coefficient using a thermomechanical analyzer (TMA) in a temperature range of 30 to 300°C.

[0061] Next, the glass powder material and the carrier (terpineol containing 5% by mass ethyl cellulose and 3% by mass tributyl acetyl citrate) were mixed and kneaded using a three-roll mill to obtain a powder material slurry. Furthermore, in order to obtain an outer coating of about 10 μm, the powder material slurry was applied to the ruthenium oxide (RuO 2 ) on an alumina substrate of a resistor, the coating film was dried and fired in an electric furnace at 640° C. for 10 minutes in a nitrogen atmosphere. The obtained substrate with an overcoat layer was used to evaluate the presence or absence of metal component precipitation and acid resistance.

[0062] Regarding the presence or absence of precipitation of metal components, the above-mentioned substrate with an outer coating was trimmed using an Nd:YAG laser (wavelength: 1064 nm), and then the trimmed portion was observed using a scanning microscope (SEM). The case where no metal components were precipitated was evaluated as "0", and the case where metal components were precipitated was evaluated as "×".

[0063] Acid resistance was evaluated as follows.

[0064] The substrate with the outer coating was immersed in 0.05 mol / L sulfuric acid at 30°C for 30 minutes, then washed with water and dried, and the mass reduction was measured to calculate the mass reduction ratio (mass reduction ratio (%) = (mass of the outer coating before immersion - mass of the outer coating after immersion) / (mass of the outer coating before immersion) × 100). In addition, if the mass reduction ratio is 0.5 mass% or less, it means that the acid resistance is excellent.

[0065] As can be seen from the table, samples No. 1 to No. 4 obtained the expected values, among which the softening point was as low as below 638°C and the linear thermal expansion coefficient was 54×10 -7 / ℃~60×10 -7 / °C. Furthermore, no metal component was precipitated, and the acid resistance was excellent. On the other hand, metal bismuth was precipitated in sample No. 5. Sample No. 6 had poor acid resistance.

[0066] Industrial Applicability

[0067] The powder material and powder material slurry of the present invention are particularly suitable for forming an outer coating layer, especially forming an outer coating layer of a chip resistor, but can also be used in other applications such as adhesives for electronic component materials and sealing materials.

Claims

1. A powder material, characterized in that: The glass composition contains, by mol%, 20% to 60% ZnO, 10% to 40% B2O3, 5% to 30% SiO2, 0.1% to 13% V2O5, 0% to 4% Al2O3, 0% to 5% Li2O+Na2O+K2O, 0% to 5% MgO, 0% to 13% CaO, 0% to 4% Bi2O3, and 0% to 1% Fe2O3, and contains substantially no PbO.

2. The powder material according to claim 1, characterized in that: The softening point of the powder material is below 640°C.

3. The powder material according to claim 1 or 2, characterized in that: The linear thermal expansion coefficient of the powder material is 50×10 -7 / ℃~80×10 -7 / ℃.

4. The powder material according to claim 1 or 2, characterized in that: The powder material is used to form an outer coating.

5. A powder material slurry, characterized in that: The powder material slurry contains the powder material according to claim 1 or 2 and a carrier.

Citation Information

Patent Citations

  • Glass for covering resistor

    JP1983064245A

  • Nonlead glass composition

    JP2007063105A

  • Lead-free low-melting-point glass composition having acid resistance

    JP2009221027A